2013
DOI: 10.1002/msc.1046
|View full text |Cite
|
Sign up to set email alerts
|

Different Wording of the Patient Global Visual Analogue Scale (PG‐VAS) Affects Rheumatoid Arthritis Patients’ Scoring and the Overall Disease Activity Score (DAS28): A Cross‐Sectional Study

Abstract: Different phrasing of the PG-VAS gives different DAS28 results. As the DAS28 is a key outcome measure, such differences have the potential to influence clinical decisions relating to eligibility for biologic agents and evaluation of new therapies. We urgently need to decide on the concept to be measured and the phrasing required to capture this. The PG-VAS phrasing should then be standardized and validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…In the case of PGA, its exact wording/phrasing was not specified when developed; however, it was suggested that it could be used for two main purposes—either a patient assessment of global health or of disease activity—stemming from the two basic concepts (Table 1) [11, 13]. Over the past years many different wordings/phrasings of PGA have been formulated, covering variations of these two concepts [1418].…”
Section: Description and Practical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of PGA, its exact wording/phrasing was not specified when developed; however, it was suggested that it could be used for two main purposes—either a patient assessment of global health or of disease activity—stemming from the two basic concepts (Table 1) [11, 13]. Over the past years many different wordings/phrasings of PGA have been formulated, covering variations of these two concepts [1418].…”
Section: Description and Practical Applicationmentioning
confidence: 99%
“…The DAS28 is one of the most commonly used composite scores in routine clinical practice; the PGA component of the score carries a small weighting of 0.014, which may still result in differences to the overall DAS28 score (the maximum difference being 1.4 when holding the other variables constant and using first a PGA-VAS score of 0 mm, then of 100 mm). French et al [11] performed a study where DAS28 was calculated in the same patients when using different PGAs. Five different versions of the PGA-VAS were assessed based on: (1) “Feeling” (“How do you feel concerning your arthritis over the last week?”); (2) Disease activity (“How active has your disease been this week?”); (3) “Well-being” (“How has your overall well-being been this week?”); (4) “Best/worst” (“If 0 is the best you have ever been and 100 is the worst you have ever been, where do you think you have been over the last week?”); and (5) “Arthritis impact measurement scales” (AIMS; “Considering all the ways your arthritis affects you….”).…”
Section: Consequences Of Different Wordings/phrasingsmentioning
confidence: 99%
“…[17,18] At 0 hour i.e. at the time of starting epidural infusion the VAS score was 0 in all the 30 (100%) patients [Table 8, 9 Figure 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OMERACT/ACR variables are tender and swollen joint counts, physician's global assessment of disease activity, inflammatory markers, and the patient's assessment of pain, disease activity and physical function. The patient's assessment of pain and disease activity are commonly measured by visual analogue scales (VAS) although the wording of the VAS have not been standardised and has been shown to vary across studies [4]. Physical function is commonly measured by the Health Assessment Questionnaire (HAQ) [5], These variables were chosen through a process of literature review and nominal groups with experts because they sample the broad range of improvement in RA (have content validity) and are all at least moderately sensitive to change [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…These variables were chosen by rheumatologists from the literature and tested for their relative contribution to changes in inflammation. Patient opinion of global health or disease is measured by a VAS, the wording of which has also been found to vary across studies and clinical practice with a potential impact on prescribing biologic therapy [4].…”
Section: Introductionmentioning
confidence: 99%